Pengaruh Komunikasi Efektif Guru dan Apresiasi Terhadap Kepercayaan Diri Anak - Retnowati, Lilis; Ajat, Ajat (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to explore how effective teacher communication and appreciation can increase children's self-confidence at TKIT Nur Sa'adah Depok. Using an associative method and a quantitative approach, this study explores the relationship between independent variables (effective teacher communication and appreciation) and dependent variables (children's self-confidence). Data were collected through questionnaires filled out by teachers and parents. The results show that there is a significant relationship between effective teacher communication and appreciation and children's self-confidence at TKIT Nur Sa'adah Depok. Teachers who are able to communicate effectively and give appreciation appropriately and at the right time can increase children's self-confidence. Teacher effective communication and appreciation have a significant effect on children's self-confidence at TKIT Nur Sa'adah Depok. Therefore, it is important for educational institutions to implement communication training for teachers and use appreciation as part of an educational strategy to increase children's self-confidence.